Adjuvanticity and protective immunity elicited by Bordetella pertussis antigens encapsulated in poly(DL-lactide-co-glycolide) microspheres. - Shahin, R (1995)
Purified Bordetella pertussis antigens, encapsulated in biodegradable poly(DL-lactide-co-glycolide) (DL-PLG) microspheres, were evaluated for their immunogenicity and ability to elicit a protective immune response against B. pertussis respiratory infection. Microencapsulated pertussis toxoid, filamentous hemagglutinin, and pertactin all retained their immunogenicity when administered parenterally. Intranasal immunization with a low dose (1 micrograms) of encapsulated filamentous hemagglutinin, pertussis toxoid, or pertactin elicited strong specific immunoglobulin G and immunoglobulin A antibody responses in respiratory secretions that were greater in magnitude than the responses elicited by the same doses of unencapsulated antigen. Intranasal immunization with as little as 1 micrograms of encapsulated pertussis antigen prior to infection reduced the bacterial recovery by 3 log10 CFU. However, intranasal immunization with the same low doses of unencapsulated antigens did not reduce infection. Intranasal administration of a combination of 1 micrograms of each of the microencapsulated pertussis antigens was more effective in reducing bacterial infection than administration of any single microencapsulated antigen. Intranasal administration of microencapsulated B. pertussis antigens elicits high levels of specific antibody coinciding with protection against infection when these microspheres are administered to the respiratory tract. These data provide evidence of the respiratory adjuvanticity of three different DL-PLC microsphere preparations, each of which contains a unique B. pertussis antigen.